Politik der Differenzen Ethnisierung, Rassismen und Antirassismus im weißen feministischen Aktivismus in Wien - Mayer, Stefanie (Politik und Geschlecht, 2018)
The author deals with practices and debates on migration and ethnic differences, racism and anti-racism in the context of feminist activism in Vienna. In a longitudinal analysis from the 1980s to the 2010s, the work examines how white feminist activists negotiate powerful ethnicized differences - in explicit speech as well as implicit action. Last but not least, the question is how these practices not only construct the 'other', but also produce the 'own'.